PENGARUH PROFESIONALITAS KEPALA SEKOLAH TERHADAP KEPUASAN KERJA GURU SEKOLAH DASAR NEGERI - Afit Fatimah (Perspektif Ilmu Pendidikan, 2014)
Preliminary study in several Government Primary Schools indicates a number of Primary School principals have low degree of professionalism and some others have high degree. Based on this fact, this research formulated a problem if there is an effect of the principal’s professionalism towards the job satisfaction of the government primary school teachers. This quantitative research was performed in Kedaung Angke, Sengkareng, West Jakarta as from 1 through 30 April 2014 employing survey method with correlational technique.The variables observed was the principal’s professionalism (X) and the government primary school teachers’ job satisfaction (Y). Based on the statistical analysis the research concluded, there is a significant effect of the principal’s professionalsm toward the government primary school teachers’ job satisfaction. The principals, therefore, are suggested to improve their professionalism to support the maximal attainment of their teachers’job satisfaction.